ЛИНГВОКУЛЬТУРОЛОГИЯ – ТИЛ БИЛИМИНИҢ ЖАҢА ТАРАЎЫ - Абдиназимов, Ш.Н. (FAN va JAMIYAT, 2020)
The article deals with the issues of language and culture as well as the formation and development of linguoculturology. Scientific works of V. Humboldt, K. Fossler, E. Sepir, G. Vinokur, E. Benvenist, A.T. Khrolenko, N.F. Alefirenko, V. Vorobyov and other scientists are reviewed. Points of view of the scientists regarding the study of the connection between language and culture are given. In addition, the author focused on the first studies in Karakalpak linguistics.